Multi‐year experiment shows no impact of artificial light at night on arthropod trophic structure or abundance. Issue 8 (27th August 2020) - Firebaugh, Ariel; Haynes, Kyle J.
Abstract: Prior studies of how artificial light at night (ALAN) alters the abundances of herbivores, predators, and other trophic groups have yielded evidence of the alteration of energy and nutrient flows through ecosystems. Because the impacts of ALAN on arthropod assemblages may be context‐dependent, there is a need for more experimental work across a range of habitat types and time frames. To examine longer‐term impacts of ALAN on community and trophic structure, we experimentally manipulated ALAN in a grassland ecosystem and compared arthropod abundance and trophic structure between plots exposed to ALAN and plots exposed only to ambient light over two years. In 2015, arthropod density was 61% higher in plots with ALAN added than in plots with no ALAN added, but this difference was not statistically significant. In 2016, arthropod densities were nearly identical between plots with ALAN added and plots not exposed to ALAN. Contrasting with prior research on ground‐dwelling arthropods, we found no evidence that the effects of ALAN on abundance differed between herbivores and predators inhabiting the canopy of grassland vegetation. To better understand the ecological consequences of ALAN, we recommend experimental manipulation of ALAN in a variety of habitat types followed by repeated sampling of trophic structure over time frames that span multiple generations for the species within the focal community.